Cerebral Infarction and Refractory Seizures in a Neonate with Suspected Zika Virus Infection. Issue 4 (April 2018) - Raymond, Adam; Jakus, Jonathan
Abstract : Congenital Zika syndrome is a set of congenital anomalies associated with Zika virus infection during pregnancy. We present the unique case of a neonate born to a suspected Zika virus–positive mother that developed an embolic stroke and medication-resistant seizures. This report may impact the evolving definition of congenital Zika syndrome.